Teachers Reflection on the Factors Contributing Their Success in Conducting Action Research - Esa Maulisakina Wilma Ariyani; Moh. Adnan Latief (Pascasarjana Universitas Negeri Malang, 2020)
Abstract: This study aimed to explore the experiences of public junior high school English teachers in Malang in conducting classroom action research in terms of the factors that contribute to their success in conducting action research. The main data of this study were collected through individual semi-structured interviews administered to 3 public junior high school English teachers in Malang, Indonesia. The findings suggest that teachers' eagerness in helping their students learning better as well as improving themselves to be better teacher may be the 'it' factor contributing to their success in conducting action research. On the basis of aforementioned findings implications were discussed and recommendations were made for the teachers, schools, and future researchers. Abstrak: Studi ini bertujuan mengeksplorasi pengalaman guru bahasa Inggris di sekolah menengah pertama negeri di Malang dalam melaksanakan penelitian tindakan kelas yang mencakup faktor-faktor yang mendasari keberhasilan mereka dalam melaksanakan penelitian tindakan. Data utama dalam penelitian ini dikumpulkan melalui wawancara individu semi terstruktur pada tiga guru bahasa Inggris di sekolah menengah pertama negeri di Malang. Hasil dari penelitian ini memberikan kesan bahwa keinginan kuat guru untuk membantu muridnya dalam belajar dan meningkatkan kemampuan dirinya untuk menjadi guru yang lebih baik mungkin menjadi faktor kunci kesuksesan mereka dalam melaksanakan penelitian tindakan. Berdasarkan hasil penemuan yang telah disebutkan implikasi didiskusian dan rekomendasi dibuat untuk guru, sekolah, dan peneliti selanjutnya.